VO#037 Quotation for additional UPVC components in plumbing works rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of revised price quotation for additional UPVC components in plumbing works of BRACU new campus project.